Rapid and ultrasensitive detection of SARS-CoV-2 spike protein based on upconversion luminescence biosensor for COVID-19 point-of-care diagnostics. (November 2022) - Li, Lihua; Song, Menglin; Lao, Xinyue; Pang, Sin-Yi; Liu, Yuan; Wong, Man-Chung; Ma, Yingjin; Yang, Mo; Hao, Jianhua
Graphical abstract: We developed a novel nanosystem composed of UCNPs and Au nanorods for capturing and detecting S protein based on the Förster resonance energy transfer fluorescence (FRET) effect. Highlights: Highly sensitive and rapid detection of spike protein was constructed based on FRET effect. The detection in the NIR region is sensitive and specific and the mechanism was illustrated. The detection system could satisfy S protein and nucleocapsid protein detection simultaneously. Abstract: Here, we firstly introduce a detection system consisting of upconversion nanoparticles (UCNPs) and Au nanorods (AuNRs) for an ultrasensitive, rapid, quantitative and on-site detection of SARS-CoV-2 spike (S) protein based on Förster resonance energy transfer (FRET) effect. Briefly, the UCNPs capture the S protein of lysed SARS-CoV-2 in the swabs and subsequently they are bound with the anti-S antibodies modified AuNRs, resulting in significant nonradiative transitions from UCNPs (donors) to AuNRs (acceptors) at 480 nm and 800 nm, respectively. Notably, the specific recognition and quantitation of S protein can be realized in minutes at 800 nm because of the low autofluorescence and high Yb-Tm energy transfer in upconversion process. Inspiringly, the limit of detection (LOD) of the S protein can reach down to 1.06 fg mL −1, while the recognition of nucleocapsid protein is also comparable with a commercial test kit in a shorter time (only 5 min). The established strategy is technically superior to those reported point-of-care biosensors in terms of detection time, cost, and sensitivity, which paves a new avenue for future on-site rapid viral screening and point-of-care diagnostics.